COMPREHENSIVE APPROACH TO STUDENT EDUCATION IN THE PROCESS OF MANUFACTURE OF PRODUCTS USING THEM ELEMENTS OF DECORATIVE AND APPLIED ARTS (Pedagogy of Higher and Secondary Education, 2008)
In article problems of the complex approach are considered at performance of products with elements decoratively an applied art.